El comercio electrónico y la recaudación del impuesto al valor agregado en el Ecuador - Paredes Caicedo, Gioconda del Rocío (2017)
With the globalization process has benefited directly the economic sector, but at the same time has observed the concern of the Tax Administrations to have legislation that is not in line with the current and limited means to control the payment of taxes in this Type of trade. One of the disadvantages that exists is the collection of VAT, due to the international movement of both buyers and sellers, tangible and intangible goods, it is difficult to locate each of these components, making it difficult to verify the elements of taxation as a taxable person, Generating event, taxable base, etc. The decision taken by the governments of each country is also important, because they will give road both the improvement of the economic sector with this new way of commercialization, so that there is a feasible tax collection without it becoming a form of tax evasion.